HAK KEWARISAN PADA KARYA CIPTA INTELEKTUAL - Hj. Hamsidar (Al-Bayyinah, 2017)
AbstractThe principal problem in this writing is how is inherit status of intellectual copyright in Islamic law and positive law. In Islamic and positive law perspective, intellectual copyright is considered as the creator property and categorized as the property which can be inheritance, even partly totally. The ownership right to the intellectual copyright with inheriting cause is considered as a way to get property legally.Kata Kunci: Kewarisan, Hak Cipta dan Intelektual